Multilevel metabolic and enzyme engineering enables efficient biosynthesis of cyanidin-3-O-glucoside from dihydroquercetin in Escherichia coli - Zhiyao Wang; Wei Xie; Ruichen Gao; Zezhong Tu; Wenyong Lou; Xiaoling Wu (Bioresource Technology, 2027)

Interpretable machine learning for optimization of ultrasound-assisted polysaccharide extraction using natural deep eutectic solvents: From yield enhancement to structural and antioxidant activity validation - Shulu Zhang; Jingting Han; Ruichen Gao; Yeqing Xu; Zheng Feng; Xinhui Huang; Yinze Zhong; Qingxia Wang; Xinran Yu; Siyu Chang; Meiting Jiang; Zhibin Wang; et al. (Bioresource Technology, 2026)

IS-RPB-intensified resource utilization of coal fly ash coupled with multidimensional techno-economic and life cycle assessment - Zhiguo Yuan; Zhong Guo; Chunge Dang; Shuli Zhang; Youzhi Liu; Ruichen Wang (Process Safety and Environmental Protection, 2026)

A review of lithium extraction from primary and secondary lithium resources using supercritical CO2 - Hongquan Wei; Jie Liu; Ruichen Wang; Yanjun Li; Yuexin Han; Chengxiu Li (Hydrometallurgy, 2026)

Cluster analysis of rock block shapes: A novel quantitative method for characterising rock mass structures - Zheqi Tian; Jun Zheng; Ruichen Zhang; Rafael Jimenez; Dongpo Wang; Jiongchao Wang (Computers and Geotechnics, 2026)

Engineering orbital coupling in rare-earth-doped layered double hydroxides for enhanced wound healing - Jiajia Jing; Yan Miao; Xiaotong Ma; Ruichen Wang; Haojie Wei; Chuxuan Liu; Kelong Fan; Jingping Zhong; Haifeng Liu (Chemical Engineering Journal, 2026)

High entropy alloy PtRuCuCoNi nanosponges with tunable electronic configurations for electrocatalytic lactic acid oxidation toward upcycling waste polylactic acid - Bingshuo Li; Xiaokun Fa; Ruichen Geng; Liuyang Jiang; Ruiping Liu; Zhihan Zhang; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2026)

Sub-2 nm ultrafine high-entropy alloy nanowires with multi-atom catalytic sites for efficient electrocatalytic upcycling of waste plastics - Xiaokun Fa; Ruichen Geng; Zhihan Zhang; Yinglong Wang; Fengbin Zheng; Shuli Yin (Chemical Engineering Journal, 2026)

Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

Tuning surface residual lithium into a Li-ion-conductive protective interphase toward stable Ni-rich cathodes - Shumin Liu; Huangzhang Zhou; Wenhao Jia; Yingjie Sun; Peng Gao; Ruichen Zhu; Yongming Zhu; Xudong Li; Liguang Wang (Chemical Engineering Journal, 2026)

3D porous cellulose/polyaniline aerogel composite as a high-performance electrode for selective electrosorption of rhenium - Ruichen Ma; Boxiao Zhao; Xiling Sun; Zhenning Lou; Junshuo Cui; Haibiao Yu; Yuejiao Wang; Weijun Shan; Xiaogeng Feng; Ying Xiong (Water Research, 2026)

Femtosecond laser-fabricated defect-rich PtRe alloy clusters for enhanced alkaline hydrogen evolution - Xianze Zhang; Junwen Xiong; Zhiyi Sun; Ruichen Lu; Zikang Su; Chen Zhang; Qimiao Zhu; Shilong Yuan; Lan Jiang; Shengjie Xia; Liquan Sun; Xingdong Wang; et al. (Chemical Engineering Journal, 2026)

Succession patterns, environmental connections, and assembly mechanisms of gut microbiota in the giant freshwater prawn (Macrobrachium rosenbergii) across lifespan - Songbao Zou; Yao Zheng; Julin Yuan; Meng Ni; Mei Liu; Dan Zhou; Qiang Gao; Mingfeng Deng; Ruichen Wang; Xin Zhang (Aquaculture, 2026)

Electron-delocalization across high-entropy alloy nanofibers for efficient electrocatalytic glycerol oxidation - Yaxuan Li; Zhihan Zhang; Ranran Wei; Xiaoying Zhang; Ruichen Geng; Fengbin Zheng; Liang Wang; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2026)

Vertical distribution of new and weathered microplastics in the water column: Implications for developing reliable sampling methods - Arghavan Beheshtimaal; Ruichen Xu; Binbin Wang; Maryam Salehi (Water Research, 2025)

Preparation and tribological investigation of self-lubricating epoxy composite containing hollow mesoporous silicon nanocapsules loaded with PAO6/Cu nano-oil - Ruichen Zhang; Luyao Wang; Chunjian Duan; Shengmao Zhang; Liyong Niu; Pingyu Zhang; Zhijun Zhang; Seeram Ramakrishna; Chuanping Gao (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Global sustainable pathway for lithium metal production: A critical review and best practice guide - Ruichen Wang; Yuexin Han; Yanjun Li; Feilong Zhang; Chunge Dang; Zhiguo Yuan; Jie Liu (Chemical Engineering Journal, 2025)

Development of a novel targeted LC-MS/MS methods for the typing of cardiac amyloidosis - Kaijuan Wang; Ruichen Liu; Li Li; Xuejing Duan; Xianglong Zhao; Hongying Cong; Xiaojing Gao; Kunlun Yin; Zhangwei Gao; Zhou Zhou (Analytica Chimica Acta, 2025)

Decoupling physicochemical-biological dynamics in marine oil spills: early adaptive microbial response to hydrodynamic forcing unveils zonal impact gradients - Ranran Dong; Xinping Wang; Ruichen Cao; Chunhui Wang; Fengshu Li; Zhifeng Wan; Peiyan Sun; Mutai Bao; Haoshuai Li (Journal of Hazardous Materials, 2025)

An Unmanned Vessel Path Planning Method for Floating-Waste Cleaning Based on an Improved Ant Colony Algorithm - Yong Li; Changjun Tang; Sen Yan; Ruichen Wang; Dongxu Gao (Journal of Marine Science and Engineering, 2025)
Efficient cleaning of floating waste using an intelligent unmanned surface vehicle is an important development trend in inland water governance. Path planning is the core of the decision-making module for unmanned surface vehicle waste cleaning and is key to achieving autonomous operation of the unmanned surface vehicle. However, due to the complexity and dynamic changes of the water surface environment, unmanned surface vehicle path planning methods for floating waste face challenges such as small size, uncertainty, and uneven distribution of floating waste. In response to the above issues, this article studies the problem of insufficient integration and low efficiency between existing path planning algorithms and target-perception modules, and designs an efficient overall path planning method for floating-waste cleaning by an unmanned surface vehicle. This method transforms the path planning problem of floating-waste cleaning unmanned surface vehicle into a Traveling Salesman Problem by setting global patrol points and tracking local targets, and proposes an improved ant colony algorithm, IACO, to solve the Traveling Salesman Problem. This article is based on the TSPLIB dataset and practical applications for experiments. The experimental results show that the proposed method has average optimal path lengths of 75.930 m, 446.555 m, and 703.759 m on the Ulysses22, eil51, and st70 datasets, respectively, which are reduced by 0.355 m, 4.108 m, and 13.575 m compared to the benchmark.

Three-dimensional simulation of wave-induced seabed liquefaction in the Chengdao area - Youqi Wang; Shengyi Jiao; Haibo Chen; Ruichen Cao; Xianqing Lv (Ocean Engineering, 2025)

Identification of active sites for formaldehyde oxidation on mesoporous Pt/CeO2 catalyst at ambient temperature and low humidity - Ruichen Wang; Chao Yu; Juanjuan Gong; Qingfa Su; Hui Chen; Canyan Yang; Shaodi Sun; Zhiwei Huang; Huazhen Shen; Huawang Zhao; Bihong Lv; Xiaomin Wu; et al. (Fuel, 2025)

Serum polychlorinated biphenyls as a risk factor for MASLD: Exploring the association and underlying mechanisms - Ruichen Yang; Qingqing Jiang; Wentao Liu; Furong Wang; Shiyi Cao (Science of The Total Environment, 2025)

Sustainable domestic sewage treatment by a reinforced soil infiltration system: Dual emphasis on pollutants and greenhouse gases - Ruichen Wang; Shuli Zhang; Hongquan Wei; Mingxiao Zeng; Zhiguo Yuan; Chunge Dang (Chemical Engineering Journal, 2025)

Palbociclib inhibits the progression of head and neck cancer and improves the Cetuximab response under specific condition in vitro and in vivo - Ruichen Li; Qi Wang; Yang Zhao; Yi Zhu; Xiaoshen Wang (Molecular Biology Reports, 2024)

Techno-economic-environmental analysis based on life cycle carbon accounting and pollutants audit for cleaner production of electrolytic manganese - Ruichen Wang; Shuli Zhang; Yajing Guo; Jingyang Liu; Feilong Zhang; Chunge Dang (Process Safety and Environmental Protection, 2024)

Defect-rich perforated PdFe bimetallene for the efficient electrochemical oxidation of glycerol - Xiaojun Chu; Ruichen Geng; Zekai Shen; Yaxuan Li; Xiaorui Fan; Zhaoyou Zhu; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2024)

A multi-target and responsive nanoplatform (MM/ZnS/ATV) combining H2S and atorvastatin for enhanced atherosclerosis therapy - Yinhong Xie; Mengchen Chi; Ruichen Dong; Sui Wu; Jinming Yang; Qin Wang; Junying Chen; Yajun Weng (Chemical Engineering Journal, 2024)

The Effect of Model Input Uncertainty on the Simulation of Typical Pollutant Transport in the Coastal Waters of China - Nan Wang; Zihan Zhao; Ruichen Cao; Xianqing Lv; Honghua Shi (Journal of Marine Science and Engineering, 2024)
Route planning to evade potential pollution holds critical importance for aquaculture vessels. This study establishes a fish-feed pollutant drift model based on the Lagrangian particle tracking algorithm and designs four sets of sensitivity experiments in the East China Sea. The research investigates the impact of model input uncertainties on the drift trajectory, centroid position, and sweeping area of the fish-feed pollutants. Numerical results indicate that the uncertainty in the background flow field significantly affects the uncertainty in the centroid position and sweeping area in the numerical simulations. Specifically, when a 35% random error is added to the background flow field, the centroid shift distance reaches its maximum, and the sweeping area also attains its largest value. The uncertainty in the background wind field affects the centroid position of particles but to a much lesser extent compared to the background flow field. When considering only the uncertainty of the background wind field, the sweeping area does not significantly differ from the control experiment as the uncertainty of the background wind field increases. The initial release position has little effect on the drift direction of the fish-feed pollutants but does affect the drift distance; it has minimal impact on the trajectory but significantly affects the final position of the pollutant centroid. By analyzing the model uncertainties, this study reveals the key factors influencing the drift of fish-feed pollutants. This information is crucial for aquaculture vessels in planning routes, considering environmental factors, and reducing potential pollution risks.

Mechanistic insight into the catalytic CO oxidation and SO2 resistance over Mo-decorated Pt/TiO2 catalyst: The essential role of Mo - Chao Yu; Canyan Yang; Ruichen Wang; Geyu Dai; Hui Chen; Zhiwei Huang; Huawang Zhao; Zuoming Zhou; Xiaomin Wu; Guohua Jing (Chemical Engineering Journal, 2024)

Engineering stable Cu+-Cu0 sites and oxygen defects in boron-doped copper oxide for electrocatalytic reduction of CO2 to C2+ products - Canyan Yang; Ruichen Wang; Chao Yu; Jinhua Xiao; Zhiwei Huang; Bihong Lv; Huawang Zhao; Xiaomin Wu; Guohua Jing (Chemical Engineering Journal, 2024)

The effects of wind-wave disturbances on sediment resuspension and phosphate release in Lake Chao - Jingxian Wang; Jisen Chai; Ruichen Xu; Yong Pang (Science of The Total Environment, 2024)

A Floating-Waste-Detection Method for Unmanned Surface Vehicle Based on Feature Fusion and Enhancement - Yong Li; Ruichen Wang; Dongxu Gao; Zhiyong Liu (Journal of Marine Science and Engineering, 2023)
Unmanned surface vehicle (USV)-based floating-waste detection presents significant challenges. Due to the water surface’s high reflectivity, there are often light spots and reflections in images captured by USVs. Furthermore, floating waste often consists of numerous small objects that prove difficult to detect, posing a robustness challenge for object-detection networks. To address these issues, we introduce a new dataset collected by USV, FloatingWaste-I, which accounts for the effects of light in various weather conditions, including sunny, cloudy, rainy and nighttime scenarios. This dataset comprises two types of waste: bottles and cartons. We also propose the innovative floating-waste-detection network, YOLO-Float, which incorporates a low-level representation-enhancement module and an attentional-fusion module. The former boosts the network’s low-level representation capability while the latter fuses the highest- and lowest-resolution feature map to improve the model robustness. We evaluated our method by using both the public dataset FloW-img and our FloatingWaste-I dataset. The results confirm YOLO-Float’s effectiveness, with an AP of 44.2% on the FloW-img dataset, surpassing the existing YOLOR, YOLOX and YOLOv7 by 3.2%, 2.7% and 3.4%, respectively.

Efficient predictor of pressurized water reactor safety parameters by topological information embedded convolutional neural network - Muzhou Hou; Wanjie Lv; Menglin Kong; Ruichen Li; Zhengguang Liu; Dongdong Wang; Jia Wang; Yinghao Chen (Annals of Nuclear Energy, 2023)

Research on the Transport of Typical Pollutants in the Yellow Sea with Flow and Wind Fields - Nan Wang; Ruichen Cao; Xianqing Lv; Honghua Shi (Journal of Marine Science and Engineering, 2023)
In this study, we developed a transport model for typical pollutants in the Yellow Sea using the Lagrangian particle tracking method to analyze the trajectories of fish feed, a common pollutant in the Yellow Sea. The model incorporates the influence of ocean currents and surface winds on pollutant transport and utilizes a series of numerical experiments to simulate pollutant transport. Through statistical analysis of the numerical experiment results, we identified characteristic circles that represent the pollutant distribution patterns. Furthermore, based on the current and wind information within these characteristic circles, we derived an empirical formula to describe pollutant distribution. This formula enables us to predict the spatial distribution of pollutants using available current and wind data. Using this empirical formula, we designed an effective path to avoid pollutant contamination. This approach not only optimizes the utilization of computational resources within the study area but also contributes to the rational planning of navigation routes for aquaculture vessels. Overall, our study provides valuable insights into the transport behavior of fish feed pollutants in the Yellow Sea. The establishment of the empirical formula and the design of effective routes to avoid pollution contribute to the efficient management of pollution and facilitate the planning of marine activities in the region.

The liquefaction pressure characteristics of silty soil in the Chengdao area: Numerical simulations - Qixiang Wang; Yupeng Ren; Ruichen Cao; Guohui Xu; Xianqing Lv (Ocean Engineering, 2023)

Triclocarban exposure aggravates dextran sulfate sodium-induced colitis by deteriorating the gut barrier function and microbial community in mice - Mengyu Qin; Hehua Lei; Yuchen Song; Mengjing Wu; Chuan Chen; Zheng Cao; Cui Zhang; Ruichen Du; Ce Zhang; Xian Wang; Limin Zhang (Food and Chemical Toxicology, 2023)

Pt single atoms and defect engineering of TiO2-nanosheet-assembled hierarchical spheres for efficient room-temperature HCHO oxidation - Xiaomin Wu; Shaodi Sun; Ruichen Wang; Zhiwei Huang; Huazheng Shen; Huawang Zhao; Guohua Jing (Journal of Hazardous Materials, 2023)

Exogenous bile acids regulate energy metabolism and improve the health condition of farmed fish - Lei Wang; Gladstone Sagada; Chenyang Wang; Ruichen Liu; Qiang Li; Chen Zhang; Yunzhi Yan (Aquaculture, 2023)

Reconstruction of catastrophic outburst floods of the Diexi ancient landslide-dammed lake in the Upper Minjiang River, Eastern Tibetan Plateau - Junxue Ma; Jian Chen; Zhijiu Cui; Wendy Zhou; Ruichen Chen; Chengbiao Wang (Natural Hazards, 2022)

Prevention of acetaminophen-induced hepatocyte injury: JNK inhibition and GSTA1 involvement - Yicong Chang; Jingshan He; Bingke Ma; Muhammad Ishfaq; Jiaqi Wang; Ruichen Zhang; Liang Yuan; Jiarui Liu; Changwen Li; Fangping Liu (Molecular & Cellular Toxicology, 2021)